2022
DOI: 10.2147/jmdh.s384072
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Coordinating Health Services for Individuals with Serious Mental Illness – A Qualitative Study

Abstract: Purpose Individuals with serious mental illness (SMI) might require coordinated health services to meet their healthcare needs. The overall aim of this study was to describe the perspectives of professionals (registered nurses, medical doctors, social educators, and social workers) on care coordination and measures to ensure proper and coordinated follow-up of the healthcare needs of individuals with SMI. More specifically, we investigated which measures are taken by employees in municipal health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These strategies can prevent or minimize the adverse impact of deterioration on individuals' health and well-being. (19).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies can prevent or minimize the adverse impact of deterioration on individuals' health and well-being. (19).…”
Section: Discussionmentioning
confidence: 99%
“… 2 This has been done by Yousef s Khader et al who found that it is necessary to have resources, equipment and supplies, documentation, staff training, and the provision of health care services to support future health services by using the method of direct observation of the hospital and interviews with staff, primary health care and hospitals in order to be able to assess and evaluate the availability of various services. 3 …”
Section: Dear Editormentioning
confidence: 99%
“…2 This has been done by Yousef s Khader et al who found that it is necessary to have resources, equipment and supplies, documentation, staff training, and the provision of health care services to support future health services by using the method of direct observation of the hospital and interviews with staff, primary health care and hospitals in order to be able to assess and evaluate the availability of various services. 3 The study conducted by Therese Dwyer Løken et al proved that knowledge of individual life situations relates to individual service recipients and their lives with diverse and complex needs and challenges related to mental health, substance abuse, physical health, and the social life in which service recipients and family caregivers increase the importance of knowing the uniqueness of each person's situation, including the individual's history, desires, goals, abilities and resources. Professionals and managers agree on the importance of having such knowledge.…”
mentioning
confidence: 99%